Attentional Focusing Instructions and Force Production - Marchant, David C. (Frontiers in Psychology, 2011)
Research progress assessing the role of attentional focusing instructions on skill acquisition and performance has lead researchers to apply this approach to force production tasks. Initial converging evidence indicates that force production tasks are sensitive to verbal instruction; externally focused instructions (onto movement outcomes, or onto the object force is being exerted against) are shown to be more beneficial than internally focused instructions (focusing attention onto the movements being executed). These benefits are observed for maximal and accurate force production, as well as the maintenance of force production in prolonged tasks. A range of mechanisms are identified supporting the proposal that an external focus promotes movement efficiency in line with energy and effort conservation. Future research is required to assess how this developing body of work interacts with the broader understanding of psychological and physiological factors implicated in the effective production, maintenance and limitation of maximal or sub-maximal forces.